MEMBACA ARAH PENDIDIKAN ASIA TENGGARA: ANALISIS KOMPARATIF PENDIDIKAN INDONESIA DAN MALAYSIA - Melawati Muhtaromah; Novi Sopirah; Sholeh Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to compare education policies in Indonesia and Malaysia by examining the structure of education levels, curriculum implementation, language of instruction, funding systems, equity of access, and teacher quality. A descriptive-comparative method was employed through the analysis of policy documents, national reports, and research findings from the last ten years. The results indicate that both countries share a strong commitment to improving the quality and equity of education, yet they adopt different policy approaches. Indonesia tends to implement more dynamic curriculum reforms and uses Indonesian as the sole national instructional language, whereas Malaysia applies more centralized policies with both Malay and English as instructional languages. In terms of funding and equity, Malaysia demonstrates greater consistency, while Indonesia faces geographical and regional disparities. Both countries continue to encounter challenges related to teacher competency and equitable education services. These findings provide a comprehensive overview of the strengths, similarities, and challenges of each country, serving as a basis for developing more effective education policies in Southeast Asia. Keywords: Education policy Indonesia and Malaysia 1, equity 2, teacher quality 3